Chalcogenide Perovskites: Tantalizing Prospects, Challenging Materials. Issue 3 (13th December 2021) - Sopiha, Kostiantyn V.; Comparotto, Corrado; Márquez, José A.; Scragg, Jonathan J. S.
Abstract: Chalcogenide perovskites have recently emerged into the spotlight as highly robust, earth abundant, and nontoxic candidates for various energy conversion applications, not least photovoltaics (PV). Now, a serious effort is required to determine if they can emulate the PV performance of the better‐known, part‐organic halide perovskites, in applications such as tandem solar cells. This review summarizes the surprisingly large body of literature pertaining to chalcogenide perovskites, which have been investigated for many years despite only recently being considered for applications. The confusing variety of claims coming from computational materials discovery is clarified, and it is specified which chalcogenide perovskites actually exist and should form the focus of experimental work. The highly interesting optoelectronic and transport properties of the known materials at their current stage of development are summarized, which makes a clear case for investigating them further. The existing synthesis literature is collated, which provides some important and possibly unnoticed clues to experimentalists grappling with these somewhat challenging materials. The authors hope that the highlighting of this information will facilitate further exciting studies, better approaches, and new progress for chalcogenide perovskites. Abstract : Chalcogenide perovskites are hitting the spotlight due to their apparently ideal properties for green energy conversion applications. These materials, with their exceptional light absorption, unmatched environmental stability and abundant constituents, have now shown indications of high efficiency potential. The authors provide a detailed review of the field, highlighting the promise, potential, and challenges faced by these novel materials.